نکاح مسیار کا تاریخی پس منظر اور ثقافتی اثرات : Historical Background and Cultural Implications of Nikah Misyar - Waheed Ullah; Dr. Sami ul Haq (Al Manhal Research Journal, 2025)
Nikah Misyar is a modern term with roots in ancient jurisprudential debates. Its legitimacy is hotly debated among contemporary scholars. Those who justify it base it on general principles of jurisprudence (permissibility of conditions, waiver of rights) and consider it a solution in specific social situations. Opponents consider it to be illegitimate, makruh, or at least undesirable, based on the objectives of marriage, women's rights, family system, and its similarity to mut'ah. Before entering into any type of marriage, especially in a controversial case like Misyar, it is essential to seek detailed advice from a reputable, informed, and balanced religious scholar on all its aspects (conditions, regulations, possible consequences, local laws). It should be remembered that having a Shariah legitimacy is not always a substitute for practical expediency and individual/family well-being.